Developing the Rationale for Including Virtual Reality in Cognitive Rehabilitation and Exercise Training Approaches for Managing Cognitive Dysfunction in MS - Wender, Carly L. A.; DeLuca, John; Sandroff, Brian M. (NeuroSci, 2022)
Cognitive impairment is a common and detrimental consequence of multiple sclerosis (MS) and current rehabilitation methods are insufficient. Cognitive rehabilitation (CR) and exercise training (ET) are the most promising behavioral approaches to mitigate cognitive deficits, but effects are small and do not effectively translate to improvements in everyday function. This article presents a conceptual framework supporting the use of virtual reality (VR) as an ideal, common adjuvant traditional CR and ET in MS. VR could strengthen the effects of CR and ET by increasing sensory input and promoting multisensory integration and processing during rehabilitation. For ET specifically, VR can also help incorporate components of CR into exercise sessions. In addition, VR can enhance the transfer of cognitive improvements to everyday functioning by providing a more ecologically valid training environment. There is a clear interest in adding VR to traditional rehabilitation techniques for neurological populations, a stronger body of evidence of this unique approach is needed in MS. Finally, to better understand how to best utilize VR in rehabilitation for cognitive deficits in MS, more systematic research is needed to better understand the mechanism(s) of action of VR with CR and ET.